PENGARUH RETURN ON ASSET TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI PADA SEKTOR PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI 2020-2023 - Karolina D.L, Jeni; Batary Citta, Andi (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
This study aims to analyze the impact of profitability on firm value in the mining sector and to evaluate whether CSR disclosure moderates this relationship. This research uses a quantitative method with a causal approach, Secondary data used in this study were obtained from financial reports of mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The study population consists of 28 companies in the Metal and Components sub-sector listed on the IDX. From this population, 18 companies were selected as samples, with data taken from the period 2016 to 2022. Data analysis shows that ROA has a significant positive impact on firm value, with a coefficient of 4.502 and a significance value of 0.003, confirming that profitability is an important factor in increasing firm value. However, CSR produced results contrary to the initial hypothesis. This indicates that CSR does not strengthen the positive effect of ROA on firm value but rather reduces it. The findings of this study provide new insights into the complexity of the relationship between profitability and firm value in the context of CSR and challenge the common understanding that CSR always enhances the positive impact of profitability on firm value.